Μικροβιολογική εξέταση παραδοσιακών τυριών (καλαθάκι, μελίχλωρο) της νήσου Λήμνου και απομόνωση στελεχών γαλακτικών βακτηρίων : - Μυλωνά, Μαρία (2014)
Since ancient times, man has, most probably by chance, been able to produce cheese from the moment milk was utilized, since the main change that occurs in milk when left at room temperature is acidification which promotes coagulation (due to denaturation and proteolytic breakdown of casein). However, in reality, in order to coagulate milk and produce cheese today, proteolytic enzymes such as rennet are required. The acidification-fermentation of cheese, as well as the well known organoleptic characteristics of each cheese (flavour, texture) are not only determined by the milk and proteolytic enzymes, but mainly by the various species of microorganisms that can grow in milk. Most cheeses are fermented products. This fermentation occurs with the help of specific strains of lactic acid bacteria, known as starter cultures. However, in some other types of cheese, fermentation takes place without any external (artificial) addition, but rather via the growth of the autochthonous lactic acid bacterial flora. The purpose of this study was the microbiological examination of samples of the traditional cheeses of the island of Limnos, most notably kalathaki and melichloro, as well as the isolation of lactic acid bacterial strains. To this end, 3 samples of kalathaki and 4 samples of melichloro were examined, resulting in the successful isolation, of 112 strains of lactic acid bacteria with the largest population of these being mesophilic and themophilic cocci. All the lactic acid bacteria that were isolated, were found to fermente lactose via the homofermentative pathway (production of lactic acid in the absence of carbon dioxide) and were able to grow up to a 6% concentration of sodium chloride (NaCl). Finally, the cheese samples were examined for the presence of pathogenic Salmonella spp., Listeria monocytogenes and Staphylococcus aureus, where populations of staphylococci were found within permissible limits, according to the legislation (Regulation (EU) 1441/2007), Salmonella and Listeria were absent from all samples.